2020
DOI: 10.1002/srin.202000128
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of a Medium‐Carbon High‐Strength Bainitic Steel Treated by Boro‐Austempering Treatment

Abstract: The microstructure and properties of a medium‐carbon high‐strength bainitic steel treated by integrated technology of austempering and boriding treatments (boro‐austempering) are investigated by metallographic method, electrochemical impedance spectroscopy, and so on. The results show that the carbide‐free bainite of substrate and the borided layers on the surface are successfully obtained by integrated boro‐austempering treatment. The hardness of surface is up to 2.5–3.0 times that of substrate and the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
4
7
0
Order By: Relevance
“…For all three treatment intervals, the microstructures were composed of plate or lath-like bainite (PB), granular bainite (GB), and blocks of martensite/ austenite (M/A). The microconstituents formed are consistent with those obtained for steels with similar chemical composition submitted to austempering treatment for 1 h [35] and also for bainitic steels submitted to other thermochemical treatments, such as boro-austempering, [12] indicating that maintenance in the CFE bath does not influence the phase transformation of the material.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…For all three treatment intervals, the microstructures were composed of plate or lath-like bainite (PB), granular bainite (GB), and blocks of martensite/ austenite (M/A). The microconstituents formed are consistent with those obtained for steels with similar chemical composition submitted to austempering treatment for 1 h [35] and also for bainitic steels submitted to other thermochemical treatments, such as boro-austempering, [12] indicating that maintenance in the CFE bath does not influence the phase transformation of the material.…”
Section: Resultssupporting
confidence: 83%
“…Studies show the efficiency of techniques such as shot peening, nitriding, and boriding thermochemical treatments for this purpose. [9][10][11][12] Another promising alternative is thermoreactive diffusion (TRD) treatment, which, as in the boriding treatment, can be directly incorporated into the austempering process without the need for a new heating step, as used, for example, in the case of tempering after quenching for saving time and energy. TRD in conjunction with the austempering treatment has already been successfully applied to vermicular and ductile cast iron, where, after removal from the TRD bath, samples were directly cooled and held at 300 C in the austempering salt bath.…”
mentioning
confidence: 99%
“…Oliveira et al [18] claimed that the boro-austempering treatment (the integrated boriding and austempering process) was a promising alternative to increase the wear resistance of advanced high-strength bainitic steels. previous study [19] indicated that the borided layers and bainite transformation in the center matrix were not significantly affected by each other during the boro-austempering treatment. From a commercial viewpoint, boro-austempering treatment has some advantages.…”
Section: Introductionmentioning
confidence: 80%
“…Since the boro-austempering treatment is successfully applied in cast irons [20,21], it has attracted much attention. However, very limited studies have been performed to fabricate high-strength bainitic steels by boro-austempering [18,19]. Though the hardness, compound phase and corrosion resistance in 0.5% NaCl of boro-austempered steels were investigated in the author's previous study [19], several related key issues remain unsolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation